Causes and therapeutic limitations of clinical alopecia and the advent of human pluripotent stem cell follicular transplantation - Hang Zhou; Yu-Xuan Zhang; Quan-Kai Lei; Yu-Mei Li; Yun-Wen Zheng (Stem Cell Research & Therapy)
Abstract Hair loss is a prevalent condition that affects many people worldwide and is often associated with self-neglect and anxiety. Hair transplantation is emerging as a viable therapeutic option for addressing several forms of hair loss that are resistant to pharmacological treatments. The etiology of hair loss is multifactorial and includes genetic predisposition, psychological factors, exposure to toxic agents, nutritional deficiencies, and mechanical stress. However, existing treatments, including topical medications, oral therapies, and phototherapy, often fail to provide comprehensive solutions. As a result, hair transplantation is currently the primary option for patients seeking a permanent solution to their hair loss. In this study, we systematically evaluated different hair follicle transplantation techniques and analyzed their respective advantages and limitations. Our results show that challenges such as limited hair follicle supply, suboptimal follicle survival rates, and recurrent hair loss hinder the effectiveness of transplantation, leaving many patients unsatisfied with the available options. Fortunately, advances in regenerative medicine, particularly the development of single-cell-integrated hair follicles or skin organoids derived from induced pluripotent stem cells, offer promising alternatives. These innovations have the potential to provide a substantial supply of uniform hair follicles tailored to the specific needs of individual patients, thereby expanding treatment options for those inadequately served by conventional methods. In summary, apart from a limited range of topical and systemic treatments, hair transplantation is often a last resort for people with hair loss. The potential to generate new hair follicles or organoids heralds a new era for large-scale clinical applications and the establishment of standardized treatment protocols.